A Novel Fibroblast Reporter Cell Line for in vitro Studies of Pulmonary Fibrosis - Nemeth, Julia; Schundner, Annika; Quast, Karsten; Winkelmann, Veronika E.; Frick, Manfred (Frontiers in Physiology, 2020)
Idiopathic pulmonary fibrosis (IPF) is a fatal disease of the lower respiratory tract with restricted therapeutic options. Repetitive injury of the bronchoalveolar epithelium leads to activation of pulmonary fibroblasts, differentiation into myofibroblasts and excessive extracellular matrix (ECM) deposition resulting in aberrant wound repair. However, detailed molecular and cellular mechanisms underlying initiation and progression of fibrotic changes are still elusive. Here, we report the generation of a representative fibroblast reporter cell line (10-4ABFP) to study pathophysiological mechanisms of IPF in high throughput or high resolution in vitro live cell assays. To this end, we immortalized primary fibroblasts isolated from the distal lung of Sprague-Dawley rats. Molecular and transcriptomic characterization identified clone 10-4A as a matrix fibroblast subpopulation. Mechanical or chemical stimulation induced a reversible fibrotic state comparable to effects observed in primary isolated fibroblasts. Finally, we generated a reporter cell line (10-4ABFP) to express nuclear BFP under the promotor of the myofibroblast marker alpha smooth muscle actin (Acta2) using CRISPR/Cas9 technology. We evaluated the suitability of 10-4ABFP as reporter tool in plate reader assays. In summary, the 10-4ABFP cell line provides a novel tool to study fibrotic processes in-vitro to gain new insights into the cellular and molecular processes involved in fibrosis formation and propagation.